Defects in TiO2 crystals - Stashans, A. (2013)
TiO2 crystals, anatase and rutile, have been studied using Density Functional Theory (DFT) and the Generalized Gradient Approximation (GGA). Also, the intraatomic interaction term for strongly correlated d-electrons (DFT+U approximation) has been utilized for a proper description of the Ti d-electrons. The presence of some impurities in the otherwise pure crystal affects the structural, electronic and magnetic properties of the TiO2. The presence of a Fe atom in the anatase structure produces shifts of the Ti atoms towards it whereas the majority of O atoms move away. Also, it exhibits n-type electrical conductivity. When a Sc atom is present in the same structure, Ti atoms are not moving while the O atoms move outwards with respect to the impurity. There are no changes in the electrical conductivity. In the case of Fe atom incorporation into the rutile structure, the host Ti atoms move towards the point defect and O atoms move outwards, obviously due to the electrostatic forces. The bandgap reduction has been observed for this particular case. Finally, the presence of a Sc atom in the rutile crystalline lattice produces a local microstructure with all defectsurrounding atoms displacing themselves outwards the defect, most due to the reduction of the charge in the defective region. A small band-gap reduction (14%) has been also found in this case.